1997
DOI: 10.1093/sleep/20.9.707
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory Response to Induced Auditory Arousals During NREM Sleep

Abstract: Sleep state instability is a potential mechanism of central apnea/hypopnea during non-rapid eye movement (NREM) sleep. To investigate this postulate, we induced brief arousals by delivering transient (0.5 second) auditory stimuli during stable NREM sleep in eight normal subjects. Arousal was determined according to American Sleep Disorders Association (ASDA) criteria. A total of 96 trials were conducted; 59 resulted in cortical arousal and 37 did not result in arousal. In trials associated with arousal, minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 0 publications
1
20
0
2
Order By: Relevance
“…Badr et al (4) reported that ventilation was unchanged during the first breath of an auditory-induced arousal and that the arousalrelated increase in ventilation occurred during the second breath of the arousal. First-breath inhibition of ventilation after arousal has also been demonstrated in dogs (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Badr et al (4) reported that ventilation was unchanged during the first breath of an auditory-induced arousal and that the arousalrelated increase in ventilation occurred during the second breath of the arousal. First-breath inhibition of ventilation after arousal has also been demonstrated in dogs (19).…”
Section: Discussionmentioning
confidence: 99%
“…Although auditory stimuli have been widely used in studies investigating the autonomic response to arousal (4,10,13,33,42), it is unlike the endogenous stimuli that induce arousal at the termination of an obstructive apnea. We chose to use the auditory stimulus because occlusion alone is unlikely to induce arousal on all occasions, and it was a standardized method of rapidly inducing cortical arousal during the two conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The arousal response is important for survival of the affected patient; however, the sleep fragmentation induced by repetitive arousals and the physiological events that surround the arousal response also have adverse consequences which contribute to the pathophysiology and clinical manifestations of SDB [5]. Arousals are characterized by abrupt changes in central nervous system activity that produce electroencephalogram (EEG) activation and marked changes in a wide range of autonomic nervous system parameters such as heart rate (HR), blood pressure (BP), ventilation and peripheral vascular resistance [6][7][8][9][10]. Arousals are typically evident and conventionally detected as changes in cortical EEG activity, a labor-intensive approach associated with high interscorer variability [11].…”
Section: Introductionmentioning
confidence: 99%
“…Of five separate studies that have investigated the breath-by-breath ventilatory responses to auditory-induced arousals in healthy subjects (10)(11)(12)(13)(14), not one found a period of significant hypoventilation (ventilation reduced .10% below baseline) after the initial hyperventilatory response, despite some subjects having flow limitation during stable sleep. In addition, airway resistance (10,11) was reduced and dilator muscle activity increased (10,14) for approximately 20-30 seconds after the brief arousal in these healthy individuals.…”
mentioning
confidence: 99%